Métodos de controle de capim-annoni - (:unkn) unknown (Universidade Federal do Pampa, 2020)
Lovegrass (Eragrostis plana Nees) is one of the main limitations of livestock activity when it comes to weeds. Based on this, the objective of this work was to test the efficiency of different chemical, physical, cultural, and integrated methods, in the control of lovegrass in a native pasture. The study was conducted in the experimental area of the Federal University of Pampa - Campus Itaqui. The experimental design was completely randomized with 15 treatments and four replications, with a control treatment totaling 60 plots of 9 m². For chemical control, 356 g ea (acid equivalent) in 1.350 L of syrup was used for the isopropylamine salt, isopropylamine salt + potassium salt, ammonium salt, di-ammonium salt, and potassium salt, for clethodim the dose used was 120 g i.a. (active ingredient) in 1.350 liters of syrup. The physical control was carried out with the application of fire, the mechanical control was carried out by mowing, leaving a residual height of 5 cm and a railing at 10 cm depth. For the cultural and integrated methods, basic fertilization was carried out, the control was made with the use of the herbicide isopropylamine salt + potassium salt in the dose 356 g a.e (acid equivalent) in 1.350 L of syrup and implanted forage species of elephant grass (Pennisetum purpureum Schum.) cv. BRS Kurumi, Pangola grass (Digitaria decumbens), Birdsfoot trefoil (Lotus corniculatus L.) cv. São Gabriel and forage peanut (Arachis pintoi). Assessments of the number of lovegrass plants per m², number of species, area of the uncovered plot (%), area of the plot occupied by lovegrass (%), relative density (%), and control by herbicides, were carried out at one year after applying the treatments. Sampled or recorded data were grouped according to their characteristics and then analyzed by means comparison and analysis of orthogonal contrasts, considering 5% probability of error. Glyphosate controls plants of lovegrass in the advanced stage of development at the dose used. Isolated control methods, except for the use of glyphosate, do not present efficient control of annoni grass plants under the conditions tested. Chemical control, associated with improved soil fertility and the implantation of pangola grass (Digitaria decumbens) controls lovegrass.
Keywords: Controle de planta daninha; Eragrostis plana Nees; Pastagem; Pasture; Weed control; CNPQ::CIENCIAS AGRARIAS